2007
DOI: 10.1074/mcp.m700171-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Proteome and Transcriptome Analysis of Developing Medicago truncatula Seeds

Abstract: A comparative study of proteome and transcriptome changes during Medicago truncatula (cultivar Jemalong) seed development has been carried out. Transcript and protein profiles were parallel across the time course for 50% of the comparisons made, but divergent patterns were also observed, indicative of post-transcriptional events. These data, combined with the analysis of transcript and protein distribution in the isolated seed coat, endosperm, and embryo, demonstrated the major contribution made to the embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
255
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(276 citation statements)
references
References 62 publications
19
255
1
1
Order By: Relevance
“…So far, 746 unique gene accession numbers identified from green and mature seeds constitute the Lotus resource. Similar 2-D gel or Sec-MudPIT-based proteomic studies of seed filling in Medicago and soybean identified 226 and 647 unique proteins, respectively (Gallardo et al, 2003(Gallardo et al, , 2007Hajduch et al, 2005;Agrawal et al, 2008). Comparing these Medicago and soybean proteins against the identified Lotus seed proteins (BLASTP e # 1 3 10 26 ), 39% of the proteins from Lotus were also identified in Medicago, and with soybean the overlap was 60%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, 746 unique gene accession numbers identified from green and mature seeds constitute the Lotus resource. Similar 2-D gel or Sec-MudPIT-based proteomic studies of seed filling in Medicago and soybean identified 226 and 647 unique proteins, respectively (Gallardo et al, 2003(Gallardo et al, , 2007Hajduch et al, 2005;Agrawal et al, 2008). Comparing these Medicago and soybean proteins against the identified Lotus seed proteins (BLASTP e # 1 3 10 26 ), 39% of the proteins from Lotus were also identified in Medicago, and with soybean the overlap was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Met synthase and several other enzymes involved in amino acids metabolism have been identified in Medicago seed development (Gallardo et al, 2003(Gallardo et al, , 2007.…”
Section: Protein Identificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttranscriptional regulatory processes such as alternative splicing, RNA processing, and other processes may affect the efficiency of translation. A generally low congruency of proteomic and transcriptional profiles has been reported previously (Gallardo et al, 2007).…”
Section: Changes In Protein and Rna Profiles Show Only A Small Overlapmentioning
confidence: 99%
“…Over latter years, several studies have focused on characterizing protein dynamics during plant development, as well as the associated genomes and transcriptomes involved (Roberts 2002;Heazlewood and Millar 2003;Chen and Harmon 2006;Gallardo et al 2007;Dam et al 2009). It has been demonstrated that proteomic analysis can generate relevant information towards elucidating the identity of those molecular mechanisms involved in developmental processes.…”
Section: Introductionmentioning
confidence: 99%